Haemogenic endothelium in infantile haemangioma. Issue 11 (5th October 2010) - Itinteang, Tinte; Tan, Swee T; Brasch, Helen; Day, Darren J
Abstract : Background: Proliferating infantile haemangioma (IH) is a tumour of the microvasculature composed predominantly of immature endothelial cells. The origin of IH is unclear, but it has been shown to express markers of both endothelial and haematopoietic lineages, and a role for endothelial progenitor cells in the aetiology of IH has been suggested. Haemangioblasts are precursors of both endothelial and haematopoietic cells, and their characterisation has identified the expression of cell surface and intracellular proteins that collectively can be used for assigning a haemangioblast phenotype. Methods: The authors used immunohistochemical staining to characterise the expression of primitive haematopoietic-associated proteins in proliferating IHs. Results and discussion: The authors show that the cells forming the capillary endothelium express markers associated with primitive haematopoietic cells. Additionally, many of these cells express the transcription factors brachyury and GATA-2, indicating a primitive mesodermal origin. They hypothesise that the immature capillaries in IH are derived from primitive mesodermal cells with haemangioblastic differentiation capabilities. The expression of primitive mesodermal, endothelial and haematopoietic markers by the cells forming the endothelium suggests that the immature capillaries that predominate in proliferating IH are a haemogenic endothelium phenotype, derived from haemangioblasts.